1992
DOI: 10.1302/0301-620x.74b1.1732245
|View full text |Cite
|
Sign up to set email alerts
|

The unstable hip and mid-lumbar myelomeningocele

Abstract: We reviewed 55 patients with mid-lumbar myelomeningocele (L3 and L4) first seen over a 17-year period from 1970 to 1986 and followed up for an average of ten years. We assessed a number of factors which might affect hip stability and ability to walk, recording the natural history of clinical and radiological hip deformity. Two-thirds of the hips had become dislocated or subluxed by the end of the first year of life, involving 86% of hips in patients with an L3 level and 45% of those with an L4 level. All the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A major factor in mid-lumbar (L3 and L4) lesions is hip instability, which results in delay in ambulation and a need for orthopaedic surgery. This has been reported by Asher & Olson 5 and locally by Fraser et al 16 Children in Cape Town are ambulant earlier than rural children, possibly because of delays in orthopaedic surgery or poor maintenance of appliances used for ambulation. Intelligence appeared to play a signi® cant role in ambulation in this study, a factor previously found not to affect ambulation in mid-lumbar lesions.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A major factor in mid-lumbar (L3 and L4) lesions is hip instability, which results in delay in ambulation and a need for orthopaedic surgery. This has been reported by Asher & Olson 5 and locally by Fraser et al 16 Children in Cape Town are ambulant earlier than rural children, possibly because of delays in orthopaedic surgery or poor maintenance of appliances used for ambulation. Intelligence appeared to play a signi® cant role in ambulation in this study, a factor previously found not to affect ambulation in mid-lumbar lesions.…”
Section: Discussionmentioning
confidence: 61%
“…Intelligence appeared to play a signi® cant role in ambulation in this study, a factor previously found not to affect ambulation in mid-lumbar lesions. 16 Thirty-® ve (44%) of the children were continent at 5 years of age, 25 with intermittent catheterization and ten without assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that most patients with sacral and low lumbar neurological lesions retain their functional walking ability regardless of associated spinal deformities [17,31,43,44]. In our study, there were two subjects with fused spines.…”
Section: Additional Orthopedic and Neurological Factorsmentioning
confidence: 61%
“…[6] Only 33% of L3 patients can walk, and then usually with ankle-foot orthoses (AFOs) and crutches, but all L4 patients are ambulatory. [7] The better walking potential of L4 patients is due to the presence of medial hamstrings that account for a third of hip extension strength. In myelomeningocele patients, unlike in those with cerebral palsy, an unstable hip does not result in painful arthritis.…”
Section: Hipmentioning
confidence: 99%